Perkembangan Embrio dan Penentuan Jenis Kelamin DOC (Day-Old Chicken) Ayam Jawa Super - Asmarani Kusumawati; Rina Febriany; Shella Hananti; Mufti Sartika Dewi; Ninik Istiyawati (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2016)
Super Javanese chicken is the result of a cross breeding between male domestic chicken and female layer chicken. . There has not been much research aboutSuper Javanese chicken embryonic development. This study attempts to provide information about embryonic development and sexing on Super Javanese chicken. This study used Super Javanese chicken fertile eggs from Java Farm, Maguwoharjo, Depok, Sleman. These eggs were incubated at temperature of 37o-38oC. Samples were observed with Neutral Red and Hematoxilin Eosine (HE) staining. The measurement of the Super Javanese chicken embryo were about length of the third finger, beak, and the length of the embryo's body. This observation obtained embryonic development of the super Javanese chicken spesifically. This concluded that Super Javanese chicken as a first generation from cross breeding has slower growth in embryonic development